Webinar National Agriculture Green House Gas (GHG) data collection in the Caribbean. Lessons Learned - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2023)
Participants: Nekelia Gregore, moderator. Shalini Marahaj, moderator. Luanne Stevens, Fellow at the Greenhouse Gas Management Institute.